Case study on groundwater monitoring at Pulau Burung landfill / Jamaluddin Bahari - Bahari, Jamaluddin (2006)
Groundwater monitoring is important to determine the groundwater quality at landfill area. Groundwater monitoring is done to ensure the landfill activity does not affect the environmental especially to groundwater. To acquire this target, the monitoring is done for 8 week continuously. The sample is collected and tested based on their physical and chemical characteristics. It is important to determine the groundwater quality which it can be contaminated by leachate from solid waste. The increasing amount of solid waste every day will produce more leachate that has high potential to contaminate the groundwater. Besides, this groundwater quality study also includes the new area that will be proposed for the development of Level 3 Sanitary Landfill. Thus comparison will be made between this new area and the present landfill area. In this research, groundwater is determined by physically and chemically especially to determine the presence of heavy metals in groundwater. Heavy metal contamination is so dangerous and harmful to any life especially to human. This study is essential in order to improve the efficiency and effectiveness of landfill system and their management to protect the environment.